Integration of gis and multicritorial hierarchical analysis for aid in urban planning: Case study of khemisset province, Morocco - Sidi Mohamed, El Amraoui; Mohamed, Rouchdi; Mourad, Bouziani; Abdelwahed, El Idrissi (Papeles de Geografía, 2017)
The present in a process is a reflection of the understanding of the process that enriches the programming of land resources for urbanization. To make the presentation of Model Objective no, I combined June Invoke on the use of the hierarchical method Multicriteria Analysis (AHP) and Geographical Information Systems (GIS). The relevance of the Adopting Process WATCH To solve the complex problems of spatial interpreter. Associate Determination of Other Criteria Discounted Objectives and Attributed Data Map Scale and Geographical Province of Khémisset Indicators of Them and You Hierarchy Allowed in Ontario Identified EVALUATE Quantitatively COMPARATOR OF OFFICE DESIGN OF DIFFERENT STORES Phenomenon SCENARIOS of study of the perimeter of the zones. This quantization is spatialised simulation obtained across and aggregating data following the multicriterion approach of the AHP crossover and weighted sum (WSM) method. Modeling the way factors weights them according to the respective participative. Process Also I adopt the possibility of the use of the atlas depenter available south of the ground For the OFFICER AND SPECIALISTS of the south assistant the choice of urbanization of destination of the vocation urbanistic of the grounds: AND FOR Urbanization to zones Preserve UO to Open to save.